Mixed pseudohalide complexes of copper(II). Crystal and molecular structure of [Cu(N-3)(NCS)(tmen)](n) and of [Cu(N-3)(NCO)(tmen)]2 (tmen = N,N,N ',N '-tetramethylethylenediamine) - Mauro, A. E.; Haddad, P. S.; Zorel, H. E.; Santos, RHA; Ananias, SR; Martins, F. R.; Tarrasqui, LHR (Kluwer Academic Publ, 2004)
The compounds [Cu(N-3)(NSC)(tmen)](n) (1), [Cu(N-3)(NCO)(tmen)](n) (2) and [Cu(N-3)(NCO)(tmen)](2) (3) (tmen = N,N,N',N'-tetramethylethylenediamine) were synthesized and studied by i.r. spectroscopy. Single crystals of compounds (1) and (3) were obtained and characterized by X-ray diffraction. The structure of compound (1) consists of neutral chains of copper(II) ions bridged by a single azido ligand showing the asymmetric end-to-end coordination fashion. Each copper ion is also surrounded by the other three nitrogen atoms: two from one N,N,N',N'-tetramethylethylenediamine and one from a terminal bonded thiocyanate group. Compound (2) decomposes slowly in acetone and the product formed [Cu(N-3)(NCO)(tmen)](2) (3) crystallizes in the monoclinic system (P2(1)). The structure of (3) consists of dimeric units in which the Cu atoms are penta-coordinated and connected by p(1,3) bridging azido and cyanate ligands. In both cases the five coordinated atoms give rise to a slightly distorted square-based pyramid coordination geometry at each copper ion. The thermal behavior of [Cu(N-3)(NSC)(tmen)](n) (1) and [Cu(N-3)(NCO)(tmen)](n) (2) were investigated and the final decomposition products were identified by X-ray powder diagrams.